«From a Merely Political to a Social Democracy». Wolfgang Abendroth, Palmiro Togliatti and the Constitutional Anti-Fascism in Post-War Italy and West Germany - Becher, Phillip (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2024)
This contribution offers a comparative reading of Italian communist leader Palmiro Togliatti’s and German Marxist political scientist Wolfgang Abendroth’s seminal texts on constitutional anti-fascism and their recommendations for societal transformation based on the post-war (West) German respective the Italian constitution as a means of safeguarding and deepening democracy. The contribution further seeks to illuminate how the currently resurgent doctrine of totalitarianism in the alleged name of “democracy” lends a liberal attire to a philo-fascist core. Wolfgang Abendroth; Anti-Fascism; Basic Law; Lelio Basso; Constitution; Democracy; Historical Revisionism; Giorgia Meloni; Palmiro Togliatti; Totalitarianism; Transformation.